Pengembangan Komoditi Cabai (Capsicum annum L) melalui Pendekatan Community Development: Community Development - Sri Widiasyih, Anugrah; Syafiruddin; Nasution, Komala Sari; Siregar, Deasy Arryannur; Harahap, Ari Ashari (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2024)
Community development as an educational approach that seeks to increase the level of awareness of local communities raises their confidence and ability to identify and resolve the problems they face. This community service activity aims to develop the chili commodity (Capsicum annum L) through a Community Development approach. The activity implementation method consists of two activities, namely (1) observation and data collection regarding data conditions related to the problem conditions and potential of chili commodities in Parau Sorat Village, Sipirok District; (2) Socialization of Chili Commodity Development through a Community Development approach. The participants in this activity were 25 people consisting of Field Agricultural Instructors (PPL), Chair and Members of the Saroha Farmers Group and lecturers in the Agribusiness Study Program, Faculty of Agriculture, Graha Nusantara University, Padang Sidimpuan. In developing a commodity, it is necessary to involve farmers not only in farming activities, but also in knowledge about farming. So that it can prepare the community with various resources, opportunities, knowledge and skills to increase the community's capacity in determining the future of their organization, as well as participating in and influencing life within the community group itself. So that the achievements of this Community Development activity are to create an independent society, able to explore and utilize the potential that exists in the area, and help the community to be free from backwardness or poverty.